2015
DOI: 10.1111/tbed.12318
|View full text |Cite
|
Sign up to set email alerts
|

Insulated Isothermal Reverse Transcriptase PCR (iiRT-PCR) for Rapid and Sensitive Detection of Classical Swine Fever Virus

Abstract: Classical swine fever (CSF) is an OIE-listed disease that can have a severe impact on the swine industry. User-friendly, sensitive, rapid diagnostic tests that utilize low-cost field-deployable instruments for CSF diagnosis can be useful for disease surveillance and outbreak monitoring. In this study, we describe validation of a new probe-based insulated isothermal reverse transcriptase PCR (iiRT-PCR) assay for rapid detection of classical swine fever virus (CSFV) on a compact, user-friendly device (POCKIT(™) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Recently, field applicable RT-PCRs [184] but also alternatives have been designed such as loop-mediated isothermal amplification (LAMP) assays [185,186,187,188,189,190], primer-probe energy transfer RT-qPCR [191,192] or recently insulated isothermal RT-qPCR [193]. Moreover, CSFV can be isolated on different permanent cell lines such as porcine kidney cell lines PK15 or SK6 (Technical Annex to Commission Decision 2002/106/EC).…”
Section: Diagnosismentioning
confidence: 99%
“…Recently, field applicable RT-PCRs [184] but also alternatives have been designed such as loop-mediated isothermal amplification (LAMP) assays [185,186,187,188,189,190], primer-probe energy transfer RT-qPCR [191,192] or recently insulated isothermal RT-qPCR [193]. Moreover, CSFV can be isolated on different permanent cell lines such as porcine kidney cell lines PK15 or SK6 (Technical Annex to Commission Decision 2002/106/EC).…”
Section: Diagnosismentioning
confidence: 99%
“…Thus, the simplicity and efficiency of the RT- iiPCR coupled with the POCKIT nucleic acid analyzer (RT-iiPCR/ POCKIT) to rapidly amplify nucleic acids under isothermal conditions suggested that this assay could be a potential alternative for detection of DENV especially in remote field settings. This system has been shown to offer sensitivity, specificity, and clinical performance comparable to those of reference real-time PCR or nested PCR methods for various microbial pathogens in various clinical sample types (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). One of the major advantages of RT-iiPCR is its simple protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Quantified plasmids were restriction digested with HindIII (10 μ/μl) or other appropriate restriction enzymes when HindIII sites were found within the amplicon (Thermo Scientific‐Fermentas, Ottawa, ON), purified using the Zymo DNA Clean & Concentrator™‐25 column kit (Zymo Research, Irvine, CA) and transcribed using the MEGAscript ® kit (Life Technologies). For FMDV, the desired gene regions were synthesized by IDT, cloned into the pGEM‐3Zf(+) vector, digested with EcoRI (Life Technologies, Thermo Scientific‐Fermentas, Ottawa, ON), amplified under the same cycling conditions by the described RT‐PCR in single‐plex and transcribed as described previously (Lung et al., ). RNA was quantified using the Qubit ® 2.0 Fluorometer and RNA broad range assay kit (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Conventional and real‐time RT‐PCR assays have been developed for CSFV (Wernike, Hoffmann, & Beer, ), ASFV (Fernández‐Pinero et al., ) and FMDV (Hole, Clavijo, & Pineda, ; King et al., ; Reid et al., ) and its differentials that include vesicular stomatitis virus (VSV; Hole et al., ; Rasmussen, Uttenthal, & Agüero, ), SVDV (Fernández et al., ; Núñez et al., ), and VESV (Reid et al., ). User‐friendly reverse transcription insulated isothermal PCR (RT‐iiPCR) assays performed on compact, field‐deployable instruments with automatic display of “+” or “−” results have also been described for CSFV (Lung et al., ) and FMDV (Ambagala et al., ). Real‐time multiplex PCR assays have been reported for the detection of FMDV and CSFV (Shi et al., ; Wernike et al., ) and other targets (Haines, Hofmann, King, Drew, & Crooke, ; Li et al., ; Rasmussen et al., ; Wernike et al., ).…”
Section: Introductionmentioning
confidence: 99%